TechTip: IAPAD - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
The Integrated Approaches to Participatory Development (IAPAD) programme has developed Participatory 3D Modelling (P3DM), a community-based tool that merges GIS-generated data, local knowledge and traditional spatial information (cognitive maps) to produc